P207 Can Holistic Interventions Improve the Care of People with Severe Chronic Obstructive Pulmonary Disease (COPD)? A Systematic Review. (19th November 2012) - Nurmatov, UB; Buckingham, S; Kendall, M; Sheikh, A; Pinnock, H
Abstract : Introduction and Objectives: People with severe COPD have a long-recognised burden of disabling physical symptoms compounded by co-morbidity, psychological distress and social isolation. We aimed to review the effectiveness of interventions designed to deliver holistic care compared to usual care for people with severe COPD. Methods: We searched 11 international electronic databases, three trial repositories and contacted a panel of international experts to locate published, unpublished and in-progress randomised controlled trials (RCTs), quasi-RCTs and controlled clinical trials (CCTs) that investigated holistic interventions designed to support patients with severe COPD in any healthcare context. Date range January 1990–March 2012; no language or geographical restrictions. Quality assessment and data extraction followed the Cochrane Collaboration method. Health-related quality of life (HRQoL) was the primary outcome. We used a piloted data extraction sheet and undertook narrative synthesis. Results: From 2, 866 potentially relevant papers, three trials met our inclusion criteria: two RCTs (from United States and Australia), and one CCT (from Thailand) studying a total of 216 patients. Critical appraisal identified a moderate (one RCT and the CCT) or high (one RCT) risk of bias. All interventions were led by nurses acting in a co-ordinating role (e.g. facilitating community support in Thailand, providing case-management in the US, or co-ordinating inpatient care in Australia). The community-based intervention in Thailand significantly improved HRQoL at three months compared to (limited) usual care (St George's Respiratory Questionnaire: intervention: 30.3±19.4 vs control 52.4±21.3 p<0.001). Significant effects in the US trial were confined to 'Physical functioning' and 'General health' sub-domains of Medical Outcomes Study Short-Form-36 at three but not six-months. There were no significant changes in the Australian trial. Conclusions: Some 15 years after reports first highlighted the substantial unmet needs of people with severe COPD, we have been unable to find robust trial evidence about interventions to address those needs. There is an urgent need to develop and evaluate interventions to deliver or enhance holistic care and improve the quality of life of people with severe COPD. Funding: Dunhill Medical Trust. HP is supported by a PCRCA Fellowship (CSO, Scottish Government).